Fundamental mechanisms of nanosecond-laser-ablation enhancement by an axial magnetic field - Farrokhi, Hamid (2020)
A steady magnetic field perpendicular to a laser beam is widely used to improve the rate and quality of laser ablation. Recently, we reported a 69-fold enhancement of laser ablation of silicon using a magnetic field parallel to a laser beam. To understand the fundamental mechanisms of that phenomenon, multipulse magnetic-field-enhanced ablation of stainless steel, titanium alloy, and silicon was performed. The influence of magnetic field varies significantly depending on the material: from 2.8-fold ablation enhancement on stainless steel and silicon to no pronounced ablation modification on titanium alloy. Those results are discussed in terms of magnetized-plasma, magneto-absorption, skin-layer, and magnetic-field-influenced transport effects. Understanding of those mechanisms is crucial for advanced control of nanosecond laser–surface coupling to improve laser micromachining.